2017
DOI: 10.4081/jphia.2017.668
|View full text |Cite
|
Sign up to set email alerts
|

A brief review on features of falciparum malaria during pregnancy

Abstract: Malaria in pregnancy is a serious public health problem in tropical areas. Frequently, the placenta is infected by accumulation of Plasmodium falciparum-infected erythrocytes in the intervillous space. Falciparum malaria acts during pregnancy by a range of mechanisms, and chronic or repeated infection and co-infections have insidious effects. The susceptibility of pregnant women to malaria is due to both immunological and humoral changes. Until a malaria vaccine becomes available, the deleterious effects of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 185 publications
(132 reference statements)
1
10
0
1
Order By: Relevance
“…That LLIN use conferred protection from moderate to severe anaemia but not from parasite infection herein may imply that LLINs nevertheless played a role in preventing malaria infection that has gone undetectable and which would have yet resulted in anaemia in this study [ 39 ]. IPT use in pregnancy has been associated with improved anaemia status in this and several other studies in Uganda [ 43 ], Ghana [ 44 46 ] and other countries [ 47 ], while administration of IPT was inconsequential in the development of maternal anaemia in other studies [ 48 ]. Herbal remedy users were 33% in this study similar to one-third rate observed in an Ibadan study of determinants of self-medication practices among pregnant women [ 49 ], but less than 67.5% in a study covering three geopolitical regions in Nigeria [ 50 ] and 68% seen in Abeokuta [ 51 ].…”
Section: Discussionsupporting
confidence: 64%
“…That LLIN use conferred protection from moderate to severe anaemia but not from parasite infection herein may imply that LLINs nevertheless played a role in preventing malaria infection that has gone undetectable and which would have yet resulted in anaemia in this study [ 39 ]. IPT use in pregnancy has been associated with improved anaemia status in this and several other studies in Uganda [ 43 ], Ghana [ 44 46 ] and other countries [ 47 ], while administration of IPT was inconsequential in the development of maternal anaemia in other studies [ 48 ]. Herbal remedy users were 33% in this study similar to one-third rate observed in an Ibadan study of determinants of self-medication practices among pregnant women [ 49 ], but less than 67.5% in a study covering three geopolitical regions in Nigeria [ 50 ] and 68% seen in Abeokuta [ 51 ].…”
Section: Discussionsupporting
confidence: 64%
“…These alterations provide a possible explanation for the disruption of pregnancy . Other infection models, such as malaria during pregnancy, indicate that macrophage accumulation in the placenta is a key determinant in the immune pathology associated with this parasite…”
Section: Decidual Immune Cells and T Gondii Infectionmentioning
confidence: 98%
“…8,9 All pregnant women are not equally susceptible to malaria; the susceptibility and severity of pregnant women to malaria is attributable to varying factors which include immunological and humoral changes, parity, maternal age, gestational age and intensity of transmission. 10 Malaria in pregnancy often leads to clinical complications with attendant effects such as low birth weight, abortion, premature delivery and maternal death. 8,11,12 Malaria in pregnancy is responsible for 5% of maternal anemia and 11% of maternal mortality in Nigeria.…”
Section: Analyses Of Case-based Surveillance Data On Malaria In Pregnancy In Plateau State Nigeria 2013-2017mentioning
confidence: 99%